'Cangiar la lira in tromba': Metaphors for Poetic Form in Torquato Tasso. (3rd July 2017) - Geekie, Christopher
Abstract: Beginning with his earliest poetic works, Torquato Tasso (1544–1595) often makes use of specific metaphors in order to reflect on his activity as a poet. For instance, he frequently employs images of musical instruments (the lyre, the trumpet, and the zampogna ) as a particularly suggestive means of differentiating between poetic forms and genres at the level of language, style, and sound. This article will analyze Tasso's use of these specific musical metaphors beginning with his earliest known lyric poetry, where the young poet presents himself as a new Virgil, potentially at odds with the aesthetic sensibilities of a vernacular literary tradition still in the process of consolidation. By shedding light on Tasso's thinking about poetry within his own poetry, this analysis will complement much of the scholarship already devoted to exploring Tasso's poetics on the basis of his prose treatises and his relationship to contemporary debates surrounding Aristotle's Poetics .